PENGARUH TEKNIK RELAKSASI OTOT PROGRESIF TERHADAP PENURUNAN TEKANAN DARAH PADA PASIEN HIPERTENSI DI RSU IMELDA - Damanik, Hamonangan (Jurnal Keperawatan Priority, 2018)
Hypertension is a persistent increase in systolic blood pressure which is 140 mmHg or more and diastolic blood pressure is 90 mmHg or more based on the examination at least three times at different times. The progressive muscle relaxation technique is to focus on a muscle activity, by identifying the muscles that are tense and then reducing tension by doing relaxation techniques to get a feeling of relaxation. This study aims to determine the effect of progressive muscle relaxation techniques on reducing blood pressure in hypertensive patients at Imelda Hospital Medan. The study was conducted in July 2018, a type of quasi-experimental study with a cross-sectional one-group approach pre-post test design. The population in this study were patients suffering from hypertension in April to June in the inpatient room of the Medan Imelda Hospital. The population in this study was 126 people. The sampling technique in this study was accidental sampling, thus the number of samples in this study were 23 people. Statistical analysis used paired t-test. The results of the bivariate analysis showed the average value of the systole before was 160.61 while the average value of the systole after 156.57 and the value of p = 0.000 <p value, meaning that there was an influence on the sistole before and after progressive muscle relaxation, the average value before the diastole was 96.22 while the mean value of diasistole after was 94.17 and p value = 0.000 <p value, meaning that there was an influence on the diasistole before and after progressive muscle relaxation. It is suggested for respondents to apply progressive muscle relaxation exercises independently and through related program.